Fluid Secretion by Malpighian Tubules of Rhodnius prolixus: Neuroendocrine Control With New Insights From a Transcriptome Analysis - Orchard, Ian; Leyria, Jimena; Al-Dailami, Areej; Lange, Angela B. (Frontiers in Endocrinology, 2021)
Rhodnius prolixus (the kissing bug and a major vector of Chagas disease) is an obligate blood feeder that in the case of the fifth instar consumes up to 10 times its unfed body weight in a single 20-minute feed. A post-prandial diuresis is initiated, within minutes of the start of gorging, in order to lower the mass and concentrate the nutrients of the meal. Thus, R. prolixus rapidly excretes a fluid that is high in NaCl content and hypo-osmotic to the haemolymph, thereby eliminating 50% of the volume of the blood meal within 3 hours of gorging. In R. prolixus, as with other insects, the Malpighian tubules play a critical role in diuresis. Malpighian tubules are not innervated, and their fine control comes under the influence of the neuroendocrine system that releases amines and neuropeptides as diuretic or antidiuretic hormones. These hormones act upon the Malpighian tubules via a variety of G protein-coupled receptors linked to second messenger systems that influence ion transporters and aquaporins; thereby regulating fluid secretion. Much has been discovered about the control of diuresis in R. prolixus, and other model insects, using classical endocrinological studies. The post-genomic era, however, has brought new insights, identifying novel diuretic and antidiuretic hormone-signaling pathways whilst also validating many of the classical discoveries. This paper will focus on recent discoveries into the neuroendocrine control of the rapid post-prandial diuresis in R. prolixus, in order to emphasize new insights from a transcriptome analysis of Malpighian tubules taken from unfed and fed bugs.